(untitled) (Journal of the College of Basic Education, 2023)
This research aimed to the Roles of Participation Breeders (Men & Women) Giving Services to the Farm Animals in AL-Rashdia District – Baghdad Governorate. The process of Building the Participation Scale stages, are: 1. literatures folders extension in field of farm animals, containing sixth field, nineteen items .the 2. apreliminary participation scale was showed to a group of (9 experts and specialized persons) in agricultural extension field, veterinary & animal products, to express their opinions about fields and items of the participation scale and its fitness. 3.: used the tri participation scale roles of participation giving services to the farm animals consists of :Always Participation , Sometimes Participation and Rare Participation, and put degrees of the tri scale participation according to: Always Participation three degrees, Sometimes Participation two degrees and Rare Participation one degree. The participation scale range between lower score (1 degree), higher score (3 degrees) and average (2 degrees). The research population is (732 Breeders) divided to (315Men) and (417Women) in (14 villages). Samples were chosen from both breeders and rural villages as follow: 1.A sample was randomly chosen using the stratified method a percentage of (20%) total numbers are (146 Breeders) as follow: (63 Men,83 Women). 2. A sample was randomly chosen a percentage of (25%) the numbers are (4 villages). . A questionnaire used to collect data’s from the sample. The statistical tools used are the Weighted Mean, Alpha cronbach coefficient. This research ended to the Roles of Participation Breeders (Men & Women) giving services to the farm animals were very active and influent, the Women participation was a higher than Men in that service. The research recommendation that aiming to support Men and Women Services to the farm animal’s fields, that reflected a positive improving productivity and production of farming system.